2023
DOI: 10.1021/acschemneuro.2c00676
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Electrochemiluminescence ELISA for Quantification of α-Synuclein Phosphorylated at Ser129 in Biological Samples

Abstract: Synucleinopathies are a group of neurodegenerative diseases including Parkinson’s disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA). These diseases are characterized by the aggregation and deposition of α-synuclein (α-syn) in Lewy bodies (LBs) in PD and DLB or as glial cytoplasmic inclusions in MSA. In healthy brains, only ∼4% of α-syn is phosphorylated at Ser129 (pS129-α-syn), whereas >90% pS129-α-syn may be found in LBs, suggesting that pS129-α-syn could be a useful biomarker f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
(90 reference statements)
0
19
0
Order By: Relevance
“…It was found that about 90% of α-Syn was phosphorylated at Ser129 in LBs, while only 4% of α-Syn contains this modification in the normal brain, 12 which indicates that the phosphorylation at Ser129 of α-Syn plays an important role in PD. 13 been carried out; however, the findings were inconsistent. Samuel et al prepared Ser129 phosphorylation (pS129) α-Syn by coexpressing polo-like kinase 2 (PLK-2) and α-Syn in E. coli and found that the pS129 α-Syn promoted in vitro fibrillation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was found that about 90% of α-Syn was phosphorylated at Ser129 in LBs, while only 4% of α-Syn contains this modification in the normal brain, 12 which indicates that the phosphorylation at Ser129 of α-Syn plays an important role in PD. 13 been carried out; however, the findings were inconsistent. Samuel et al prepared Ser129 phosphorylation (pS129) α-Syn by coexpressing polo-like kinase 2 (PLK-2) and α-Syn in E. coli and found that the pS129 α-Syn promoted in vitro fibrillation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…50,51 For instance, the concentration of phosphorylated α-Syn was reported to be higher in PD patients than in healthy individuals (∼756.8 vs ∼143.4 ng/mL). 52 The low abundance of this protein has made measurement with existing tools challenging, including conventional chemiluminescence and ELISA. 4,53 ■ METHODS AND MATERIALS Reagents and Materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies have suggested that serum α-Syn is a biomarker for individuals at the risk of developing PD . All three subtypes (α, β, and γ) of this protein were indicated to have clinical values. , Furthermore, the phosphorylation of α-Syn was a key indicator of the pathological progression of PD. , For instance, the concentration of phosphorylated α-Syn was reported to be higher in PD patients than in healthy individuals (∼756.8 vs ∼143.4 ng/mL) . The low abundance of this protein has made measurement with existing tools challenging, including conventional chemiluminescence and ELISA. , …”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigating CNS‐originating EV biomarkers have used serum (Dutta et al, 2021; Dutta, Hornung, Taha, Biggs, et al, 2023; Dutta, Hornung, Taha, & Bitan, 2023; Jiang et al, 2021; Taha et al, 2023; Taha & Ati, 2023) and/or plasma (Fiandaca et al, 2015; Pulliam et al, 2019; Shi et al, 2014; Taha & Ati, 2023) as media for immunoprecipitation of the EVs directly or as part of a two‐step procedure where EVs are first isolated and CNS‐originating EVs are then immunoprecipitated using specific antibodies. However, potential differences between these two media and their implications for downstream analysis have not been thoroughly investigated despite previous studies showing that preanalytical variations can affect the number of larger‐sized and smaller‐sized EVs isolated from blood (Baek et al, 2016; György et al, 2014; Jayachandran et al, 2012; Karimi et al, 2022; Lacroix et al, 2012; Liu et al, 2018; Palviainen et al, 2020; Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%